Latent profile analysis of psychological help-seeking stigma and influential factors among Hainan medical students - Yingqi Li; Jiangyou Long; Shuting Huang; Hongbing Xu; Kaixin Wangzhou; Lei Qiu (PLoS ONE, 2025)
Objective Medical students frequently confront a range of psychological challenges inherent to their profession. Among these, the psychological help-seeking stigma (PHSS) is a crucial yet often neglected barrier, impeding medical students from obtaining necessary psychological support. This research aims to elucidate the characteristics of PHSS in medical students through latent profile analysis (LPA), examine its psycho-social determinants, and establish the threshold for PHSS using receiver operating characteristic (ROC) analysis. Methods A cross-sectional survey was conducted among 3650 medical students from three medical colleges in Hainan Province, China, between February and July 2023. The survey gathered data on demographic details, PHSS, family socioeconomic status, professional help-seeking attitude, mental health level, self-efficacy and family function. LPA was employed to categorize distinct stigma profiles. Univariate and multiple logistic regression analyses were utilized to investigate the factors influencing these PHSS profiles. ROC analysis was executed to determine the optimal cut-off value for PHSS. Results Three distinct PHSS profiles emerged among the participants: “low-level stigma” (23.2%), “moderate-level stigma” (53.2%), and “high-level stigma” (23.6%). Logistic regression analysis revealed that professional help-seeking attitude, mental health level, self-efficacy and family function were associated with PHSS. The ROC analysis determined that the optimal cut-off value for identifying PHSS was ≥  19.5. Conclusion This study highlights the substantial variability in PHSS among medical students. The identification of key influencing factors underscores the need for bespoke mental health interventions tailored to this unique demographic.